Web Service Untuk Transaksi Data Pada Aplikasi Fasilitas Keuangan Dengan Metode REST - Darmawan, Diki; Kusumah, Fitrah Satrya Fajar; Ikhsan, Safaruddin Hidayat Al (STIKOM Tunas Bangsa Pematangsiantar, 2021)
According to Law No. 14/1967 concerning banking principles, it is explained that financial institutions are all entities that carry out their activities in the financial sector. withdraw money from the people and channel it into the people. Financial institutions have large data on financial facilities. In order to improve the quality of information disclosure to the public, financial institutions require the application of financial facilities as a means to register the financial facilities they have. This financial facility application consists of two platforms, namely web-based and mobile-based, so that a mechanism is needed to process data transactions between different platforms and can support interoperability between systems. Web service is a standard used in conducting data transactions between systems, because applications that exchange data can be written in a variety of programming languages and run on a variety of different platforms. The financial facility web service is built using node js with asynchronous javascript programming language so that it has better performance in handling requests. In this study, the web service was built using a REST architecture that uses the HTTP protocol to exchange data. Tests have been carried out to see the results of the web service using insomnia software. The results of this study indicate that web services can be a bridge for communication and data transactions between financial facility search applications and can run well and are able to support interoperability between systems.